1989
DOI: 10.1007/bf01536048
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related alterations in aged gut-associated lymphoid tissues in mice

Abstract: To study whether senescence-induced changes in the gut-associated lymphoid tissue (GALT) are mainly quantitative, several parameters were examined in three age groups of BALB/c mice (1-2, 12-14, and 24-28 months old). A substantial senescence-associated decline in the number of lymphoid cells was found in the mesenteric lymph nodes (MLN) and spleen (SPN), and especially in the Peyer's patches (PP), but not in the lamina propria (LP). The distribution of lymphocyte subsets in these tissues was also altered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Follicle weight and the yield of PP lymphocytes have been reported to decline with increasing age in mice (Kawanishi and Kiely, 1989). However, our own studies have shown that neither the number of PPs in young adult, mature and senescent rats, i.e.…”
Section: Aging and Intestinal Immunitymentioning
confidence: 71%
“…Follicle weight and the yield of PP lymphocytes have been reported to decline with increasing age in mice (Kawanishi and Kiely, 1989). However, our own studies have shown that neither the number of PPs in young adult, mature and senescent rats, i.e.…”
Section: Aging and Intestinal Immunitymentioning
confidence: 71%
“…Populations of CD4 Ļ© and CD8 Ļ© T cells within the Peyer's patches, naĆÆve CD4 Ļ© cells within the MLN, and IL-2 production do not show the same age-associated decline as seen elsewhere (6,11,21,32). However, reduced numbers of Th2 cells and lower levels of Ag-specific IgG and IgA have been noted within the GALT (22,28). To ascertain whether these reported changes within the GALT influence the immune response occurring in the context of parasite invasion of intestinal mucosa and to confirm whether the altered cytokine milieu seen is real and not an artifact of ex vivo restimulation we looked directly at cytokine protein and mRNA production within cecum.…”
Section: Discussionmentioning
confidence: 84%
“…The ability to secrete IgA into the saliva in humans does not diminish significantly with age [Finkelstein et al, 1984], nor does the total amount of secreted IgA in the intestine of old mice compared to IgG [Kawanishi and Kiely, 1989].…”
Section: Introductionmentioning
confidence: 96%